The Dynamics of Vowel Hypo- and Hyperarticulation in Swedish Infant-Directed Speech to 12-Month-Olds - Marklund, Ellen; Gustavsson, Lisa (Frontiers in Communication, 2020)
Vowel hypo- and hyperarticulation (VHH) was investigated in Swedish infant-directed speech (IDS) to Swedish 12-month-olds using a measure that normalizes across speakers and vowels: the vhh-index. The vhh-index gives the degree of VHH for each individual vowel token, which allows for analysis of the dynamics of VHH within a conversation. Using both the vhh-index and traditional measures of VHH, the degree of VHH was compared between Swedish IDS and ADS. The vowel space area was larger in IDS than in ADS, and the average vhh-index as well as the modal value was higher in IDS than in ADS. Further, the proportion of vowel tokens that were highly hyperarticulated (vhh-index > 75th percentile) were fewer in ADS than in IDS. Vowels in Swedish IDS to 12-month-olds are thus concluded to be hyperarticulated compared to vowels in Swedish ADS, both in terms of degree and frequency. Findings are in line with previous reports on VHH in Swedish IDS as well as on VHH in IDS to infants around 12 months in other languages. The study considers the importance of robust formant estimation, highlights the need for replication of studies on VHH in IDS on previously studied languages and ages, and discusses the benefits of the vhh-index. Those benefits include that it normalizes across speakers and vowels, can be used for dynamic measures within speech samples, and permits analyses on token-level.